Endothelial β-Catenin Deficiency Causes Blood-Brain Barrier Breakdown via Enhancing the Paracellular and Transcellular Permeability - Hussain, Basharat; Fang, Cheng; Huang, Xiaowen; Feng, Ziying; Yao, Yuxuan; Wang, Yu; Chang, Junlei (Frontiers in Molecular Neuroscience, 2022)
Disruption of the blood-brain barrier (BBB) causes or contributes to neuronal dysfunction and several central nervous system (CNS) disorders. Wnt/b-catenin signaling is essential for maintaining the integrity of the adult BBB in physiological and pathological conditions, including stroke. However, how the impairment of the endothelial Wnt/b-catenin signaling results in BBB breakdown remains unclear. Furthermore, the individual contributions of different BBB permeability-inducing mechanisms, including intercellular junction damage, endothelial transcytosis, and fenestration, remains unexplored. Here, we induced b-catenin endothelial-specific conditional knockout (ECKO) in adult mice and determined its impact on BBB permeability and the underlying mechanism. b-catenin ECKO reduced the levels of active b-catenin and the mRNA levels of Wnt target genes in mice, indicating downregulation of endothelial Wnt/b-catenin signaling. b-catenin ECKO mice displayed severe and widespread leakage of plasma IgG and albumin into the cerebral cortex, which was absent in wild-type controls. Mechanistically, both the paracellular and transcellular transport routes were disrupted in b-catenin ECKO mice. First, b-catenin ECKO reduced the tight junction protein levels and disrupted the intercellular junction ultrastructure in the brain endothelium. Second, b-catenin ECKO substantially increased the number of endothelial vesicles and caveolae-mediated transcytosis through downregulating Mfsd2a and upregulating caveolin-1 expression. Interestingly, fenestration and upregulated expression of the fenestration marker Plvap were not observed in b-catenin ECKO mice. Overall, our study reveals that endothelial Wnt/b-catenin signaling maintains adult BBB integrity via regulating the paracellular as well as transcellular permeability. These findings may have broad applications in understanding and treatment of CNS disorders involving BBB disruption.